A chelate complex‐enhanced luminol system for selective determination of Co(II), Fe(II) and Cr(III). (19th June 2012) - Kim, Kyung Min; Kim, Young Ho; Oh, Sang‐Hyub; Lee, Sang Hak
ABSTRACT: A determination method for Co(II), Fe(II) and Cr(III) ions by luminol‐H2 O2 system using chelating reagents is presented. A metal ion‐chelating ligand complex with a Co(II) ion and a chelating reagent like ethylenediaminetetraacetic acid (EDTA) produced highly enhanced chemiluminescence (CL) intensity as well as longer lifetime in the luminol‐H2 O2 system compared to metals that exist as free ions. Whereas free Cu(II) and Pb(II) ions had a strong catalytic effect on the luminol‐H2 O2 system, significantly, the complexes of Cu(II) and Pb(II) with chelating reagents lost their catalytic activity due to the chelating reagents acting as masking agents. Based on the observed phenomenon, it was possible to determine Co(II), Fe(II) and Cr(III) ions with enhanced sensitivity and selectivity using the chelating reagents of the luminol‐H2 O2 system. The effects of ligand, H2 O2 concentration, pH, buffer solution and concentrations of chelating reagents on CL intensity of the luminol‐H2 O2 system were investigated and optimized for the determination of Co(II), Fe(II) and Cr(III) ions. Under optimized conditions, the calibration curve of metal ions was linear over the range of 2.0 × 10 ‐8 to 2.0 × 10 ‐5 M for Co(II), 1.0 × 10 ‐7 to 2.0 × 10 ‐5 M for Fe (II) and 2.0 × 10 ‐7 to 1.0 × 10 ‐4 M for Cr(III). Limits of detection (3σ/s) were 1.2 × 10 ‐8, 4.0 × 10 ‐8 and 1.2 × 10 ‐7 M for Co(II), Fe(II) and Cr(III), respectively. Copyright © 2012 John Wiley & Sons, Ltd.